(untitled) (Journal of Universal Science Research, 2024)
In our time, the development of a system for monitoring the parameters of the production environment is of great relevance and importance in the current industrial environment for several reasons. First of all, the measurement and analysis of the parameters of the vibrational medium make it possible to ensure the safety of workers and avoid possible accidents and unsafe situations. In other words, monitoring systems allow you to optimize industrial processes by continuously monitoring parameters in real time. This allows you to detect possible malfunctions or anomalies in the plant and immediately respond to them, so as to avoid wasting time and resources. In this article authors propose a program algorithm for parameters of industrial premises monitoring system.